ZMEدور ريادة الأعمال – القيادة – في إدارة الأزمات بالمؤسسة دراسة حالة مؤسسة زغداني متعددة الوظائف - روميسا حرشاني; أمينة بوتمجت (My University, 2022)
This study centered on the role of entrepreneurship-leadership - in crisis management in the enterprise, and in order to achieve the goal of research and test the validity of its hypotheses, a case study was conducted for an emerging institution zme (enterprise zeghdani (multifonction des semences). The problem revolved around the key question: how can the administrative leader maintain the Organization's viability and stability in a time of crisis? The purpose of this research is to know the impact of leadership characteristics in crisis management. The research concluded, among other conclusions and recommendations, that leadership is a constant source and asset that promotes competitive advantage among organizations. After analysis, there is an impact on some of the pioneering characteristics of crisis management. Self-control has been one of the most important characteristics of a leader in crisis management. .......................................................